2012
DOI: 10.1530/joe-11-0310
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone promotes focal adhesion formation and migration in breast cancer cells through induction of protease-activated receptor-1

Abstract: Progesterone and progestins have been demonstrated to enhance breast cancer cell migration, although the mechanisms are still not fully understood. The protease-activated receptors (PARs) are a family of membrane receptors that are activated by serine proteases in the blood coagulation cascade. PAR1 (F2R) has been reported to be involved in cancer cell migration and overexpressed in breast cancer. We herein demonstrate that PAR1 mRNA and protein are upregulated by progesterone treatment of the breast cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…In previous studies, progesterone increased the proliferation of mammary gland and pancreatic cells [19,20]. In addition, progesterone stimulated the proliferation of steroid receptor-positive breast cancer and increased the migration of breast cancer cells [21,22]. Progesterone also enhanced the immunoregulatory activity of mesenchymal stem cells [23].…”
Section: Introductionmentioning
confidence: 76%
“…In previous studies, progesterone increased the proliferation of mammary gland and pancreatic cells [19,20]. In addition, progesterone stimulated the proliferation of steroid receptor-positive breast cancer and increased the migration of breast cancer cells [21,22]. Progesterone also enhanced the immunoregulatory activity of mesenchymal stem cells [23].…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, these increased PAR-1 levels are associated with disease progression and reduced overall survival in breast and lung cancer patients (9,10).…”
mentioning
confidence: 99%
“…A description of these genes and their association with the regulation of actin cytoskeleton pathway components are provided in Supplementary file 4. 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39 As a number of genes known to be associated with the actin cytoskeleton pathway were differentially regulated between the HDACi-sensitive and resistant HMCL, we postulated that the targeting of single genes among those identified would be unlikely to reverse resistance to HDACi, rather it is the global effect of these factors that mediates HDACi resistance. The genes that we identified that are differentially regulated are associated with pathways that are integral to the regulation of actin cytoskeleton rather than being components of the latter.…”
Section: Resultsmentioning
confidence: 99%